Analysis of Public Service Performance Risk Management in DPMPTSP Bandung District - Ashshiddiqi, Muhammad Taufan; Nurazizah, Allifa; Muthmainah, Annisa; Saadah, Elis Nur (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Risk management in public services, especially at the Investment and One-Stop Integrated Service Agency (DPMPTSP) of Bandung Regency, plays a key role in enhancing the effectiveness and efficiency of services provided to the community. Although the licensing system has been integrated into the online platform SAMIRINDU, there are still complaints about the lengthy licensing process, indicating room for improvement in service quality. This study aims to analyze the risks affecting public service performance and find solutions to overcome them, in hopes of assisting the DPMPTSP of Bandung Regency in achieving and maintaining high service standards. The research methodology is a qualitative case study approach, with data collection through observation, in-depth interviews, and documentation. The study results show that the application of the balanced scorecard concept in performance management analysis successfully created a balance between financial aspects, customer satisfaction, internal process efficiency, and learning and growth. The integration of risk management analysis provides a new perspective in identifying and overcoming obstacles, thus enabling the DPMPTSP to be more responsive to community needs and adaptive to operational environmental dynamics.